Human Papillomavirus Infection and Vaccination: Knowledge and Attitudes among Nursing Students in Italy - Pelullo, Concetta Paola (Int J Environ Res Public Health, 2019)
This cross-sectional study assessed nursing students’ knowledge and attitudes about Human papillomavirus (HPV) infection and vaccination in Italy. The survey was conducted among a sample of 556 nursing students. Almost all reported that they had heard about HPV infection, while only 36.5% knew the risk factors of HPV infection and that this could be prevented by the HPV vaccine. Those who had heard about HPV infection during their degree program were more likely to know risk factors of HPV infection and that this could be prevented by the HPV vaccine. The majority of students (65.3%) reported that they would be willing to receive the HPV vaccine. Moreover, 91.7% of participants reported that they were willing, as future health care operators, to recommend the HPV vaccine to others. Those who knew risk factors of HPV infection and that this could be prevented by the HPV vaccine, and those who knew that cervical cancer could be prevented by the HPV vaccine expressed this positive attitude about willingness to recommend the HPV vaccine. These results highlight the need to supplement nursing students’ specific education, to improve their knowledge and awareness of HPV vaccination.